Effects of duration of phenytoin administration on mRNA expression of cytochrome P450 and P-glycoprotein in the liver and small intestine of rats - Atsushi Kawase; Hiroyuki Tanaka; Toru Otori; Kenji Matsuyama; Masahiro Iwaki (Elsevier, 2016)
Phenytoin (5,5-diphenylhydantoin; DPH) induces expression of cytochromes P450 (CYPs). Interactions between DPH and tacrolimus suggested that the persistence of CYP induction after discontinuation of DPH is dependent on the history of administration and dosing period of DPH. However, the relationship between the duration of DPH administration and expression of CYPs in the liver and small intestine of rats is not known. Alterations in levels of P-glycoprotein (P-gp; MDR1; ABCB1) as well as CYPs cause drug interactions in the small intestine. We examined the effects of the duration of DPH administration on expression of CYPs and P-gp in the liver and small intestine of rats. Rats were treated with DPH (100 mg/kg, peroral (p.o.) twice a day (b.d.)) for 2, 4, 8, and 16 d. mRNA levels of CYPs and P-gp were examined using the total RNA extracted from the liver and duodenum 2 h and 24 h after the final administration of DPH. CYP3A activities were determined using microsomes. DPH administration for 2 d and 4 d markedly increased mRNA levels of CYPs such as CYP3A1, CYP3A2, CYP2B1, and CYP2B2 in the liver. A relatively long duration of DPH administration (8 d and 16 d) resulted in abolition of the induction of hepatic CYP but increased CYP3A activities were maintained. These results suggest that the duration of DPH administration could be an important determinant of hepatic CYP induction.